Relevansi Ajaran Tasawuf Bagi Kehidupan Muslim di Era Modern - Waskito, Puthut (el-Tarbawi, 2021)
This research is based on the fact that materialistic culture is in rise and spread across Muslim society. Almost all aspects of life are judged only by material measures. On that basis, the author sees the relevance of Sufi teachings. This research is conduct through library research methode. The primary data sources in this study are Sufi literature and the social condition of Muslim community. The secondary data sources were obtained from several writings from Sufis observer and the results of Sufi practitioners in alleviating various problems and providing various solutions to the society. The results of this study indicate that the morals of Sufism as exemplified by the Prophet Muhammad are very relevant if applied to the current modern era. In addition, various ahwal conditions or spiritual conditions such as qurbah, khauf and raja' can contribute to peace of mind and human peace in everyday life in today's modern era. Especially it can reduce the condition of the soul which always refers to the aspect of materialism which is only focused on outward needs. Keywords: Sufism teaching; Noble character; Materialism; Modern Era.